2018
DOI: 10.1371/journal.pone.0206257
|View full text |Cite
|
Sign up to set email alerts
|

Body fluid volume homeostasis is abnormal in pregnancies complicated with hypertension and/or poor fetal growth

Abstract: ObjectivesTo evaluate body water volumes and cardiac output in each trimester of pregnancies complicated with hypertension and/or poor fetal growth, relative to uncomplicated pregnancy.MethodsIn this semi-longitudinal cohort study, a standardised non-invasive maternal hemodynamics assessment in first, second or third trimester was performed in 1068 women with uncomplicated pregnancy (UP), 75 with early onset (EPE) and 117 with late onset preeclampsia (LPE), 139 with gestational hypertension (GH), 129 with smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 45 publications
0
22
0
10
Order By: Relevance
“…; Gyselaers et al . ). In contrast, plasma volume (PV) expansion is known to be less pronounced in preeclampsia than in uncomplicated pregnancy (De Haas et al .…”
Section: Cardiorenal Syndromesmentioning
confidence: 97%
See 1 more Smart Citation
“…; Gyselaers et al . ). In contrast, plasma volume (PV) expansion is known to be less pronounced in preeclampsia than in uncomplicated pregnancy (De Haas et al .…”
Section: Cardiorenal Syndromesmentioning
confidence: 97%
“…During pregnancy, total body water increases due to expansion of all maternal body fluid compartments (Davison, 1997). Bio-impedance measurements have shown that overall total body water increase is more pronounced in preeclampsia than in normal pregnancy and that this effect is more pronounced in the third trimester with late-compared to early-onset preeclampsia (Yasuda et al 2003;Levario-Carrillo et al 2006;Gyselaers et al 2018). In contrast, plasma volume (PV) expansion is known to be less pronounced in preeclampsia than in uncomplicated pregnancy (De Haas et al 2017), but increased PV has also been reported in late preeclampsia (Friedberg & Lutz, 1963;Schrier & Briner, 1991) with or without persistence of high cardiac output (Easterling et al 1990;Bosio et al 1999).…”
Section: Direct Cardiorenal Interactionsmentioning
confidence: 99%
“…Результати як більш ранніх, так і останніх досліджень демонструють, що істотне збільшення об'єму ЗВО і ПКР відбувається впродовж останніх двох триместрів вагітності. ВКР також змінюється і досягає максимального значення в кінці третього триместру [5,6]. Зміни ЗВО більшість науковців пояснюють затримкою води в молочних залозах, малому тазі та плазмі крові для забезпечення нормального перебігу пологів та післяпологового періоду.…”
Section: акушерство та гінекологіяunclassified
“…За величиною їх реактивної складової додатково розраховують значення основного обміну та активної клітинної маси [10]. У численних зарубіжних публікаціях доведено безпечність застосування біоімпедансометрії (БІМ) у вагітних та точність і надійність проведення БІА складу тіла порівняно з еталонними методиками [6,11,12] 93 (60,8±3,9 %) жінки були першонароджуючими і 62 (40,5±4,0 %) -з повторними пологами. Середній вік пацієнток становив (28,3±5,1) року (95 % Cl 27,5-29,1).…”
Section: акушерство та гінекологіяunclassified
See 1 more Smart Citation